Sperm quality parameters and oxidative stress: Exploring correlation in fluoride-intoxicated rats - Imtiaza Khan (Wolters Kluwer Medknow Publications, 2022)
Background: Assessment of male fertility needs evaluation of sperm quality parameters, namely sperm count, viability, motility and morphology. Aims: The present study aimed to analyse and correlate oxidative stress with sperm quality parameters. Settings and Design: The male Wistar albino rats, weighing between 100 and 150 g, were employed in the present study under the Committee for the Purpose of Control and Supervision of Experiments on Animals guidelines with ethical clearance from the Institutional Ethical Committee. These rats were categorised into four groups with six rats in each as control and test animals. Materials and Methods: Young male Wistar albino rats, weighing between 100 and 150 g, were divided into four groups of six rats each. The first group of rats served as control (n = 6) and was maintained under normal laboratory condition and was provided with clean drinking water, whereas rats in the second (n = 6), third (n = 6) and fourth (n = 6) groups were orally intubated with sodium fluoride of 100 ppm, 200 ppm and 300 ppm, respectively, for 40 days. Statistical Analysis Used: After the treatment period of 40 days, animals were sacrificed and alterations in sperm quality parameters were analysed by complete randomised design SAS 9.4 and Statistical Package for the Social Sciences (SPSS) IBM 17 and judged significant if P < 0.05. Results: In the experiment, a negative correlation emerged between sperm motility, viability, count versus malondialdehyde (MDA) levels, whereas the level of MDA has a positive correlation with sperm abnormalities. Sperm motility, viability and count were positively correlated with activities of superoxide dismutase and catalase, whereas decreased activities of antioxidants were related to increased sperm morphological abnormalities. Conclusion: These results suggest that MDA causes a decline in sperm motility, count and viability and an increase in morphological abnormalities via oxidative damage of membrane lipids.